PERANCANGAN SISTEM INFORMASI BOOKING FOTO STUDIO CELEMBU DI CIKANDE BERBASIS WEB MENGGUNAKAN FRAMEWORK CODEIGNITER - Fitriani, Dewi; Sigit Auliana; Gagah Dwiki Putra Aryono (Jurnal Multimedia dan Teknologi Informasi (Jatilima), 2025)
In the digital era, many people require photography services for various needs, such as family events, business purposes, or personal use. However, the manual method of booking a photo studio is considered impractical because it requires visiting the studio in person or engaging in back-and-forth communication, which is time-consuming. This study aims to design a web-based photo studio booking system to simplify the process for customers in selecting services, checking schedules, and placing bookings independently. The system is also equipped with a digital gallery and a studio availability calendar that can be accessed anytime. This research applies a qualitative approach, using data collection techniques such as in-depth interviews with the studio owner and observation of the ongoing workflow. The system development follows a systematic waterfall approach, while the CodeIgniter framework is chosen for its support of the MVC structure, which facilitates system development and maintenance, as well as its broad community support. The results show that the developed system significantly simplifies the photo studio booking process. It effectively addresses the issues of manual booking, particularly in terms of saving time and improving accessibility.